KAJIAN KRIMINOLOGIS TERHADAP PEKERJA MIGRAN INDONESIA (PMI) DI KABUPATEN KUPANG YANG MEMILIH JALUR ILEGAL UNTUK BEKERJA DI LUAR NEGERI - Putry, Zafira Amalia; Wilhelmus, Bhisa V; Djara Dima, Adrianus (Petitum Law Journal, 2025)
This research aims to analyze the factors that cause Indonesian Migrant Workers (PMI) in Kupang Regency to choose illegal routes to work abroad, the impacts experienced by illegal PMI if they become victims abroad, as well as countermeasures taken by the government to prevent PMI from choosing illegal routes. The research method used is empirical juridical with a case and conceptual approach. Data was collected through interviews, observation and document study. The research results show that the main factors for PMI choosing the illegal route are the faster and easier departure process, as well as their low level of education which makes them vulnerable to the persuasion of brokers. Illegal PMI do not receive the legal, economic, social and health protection that should be their right. The impacts experienced include violence, exploitation and lack of guarantees of safety. Mitigation efforts carried out by the government include promoting safe migration, collaborating with religious and community institutions, as well as increasing supervision and legal protection. The conclusion of this research is the importance of increasing public awareness about the risks of working through illegal channels and the need to improve the government's system of protecting and placing PMI. The advice given is for PMI candidates to ensure registration through legal channels to get proper protection.